The Performance of Resistance Progressive Collapse Analysis for High-Rise Frame-Shear Structure Based on OpenSees - Qiang Zhang; Yaozhuang Li (Shock and Vibration)
A finite element model (FEM) of frame-shear structure was constructed using OpenSees program based on the nonlinear flexibility theory and multi-vertical-line theory that considered bending-shear coupling, and its progressive collapse resistance under abnormal conditions was analyzed. Flexibility-based method for modeling shear wall finite element and multi-vertical-line element (SFI-MVLEM) was proposed. Method of deleting failure component elements was presented, as well as the model solving algorithm. The FEM was validated by the completed structure test. On these bases, 3 groups of typical frame-shear structure systems were designed to perform nonlinear dynamic collapse analysis under different initial failure conditions, in order to study the impact of the number of floors and earthquake resistant design on the progressive collapse resistance of frame-shear structures. Analysis results showed that, at initial failure of frame column, the residual shear wall element can well complete the internal force redistribution of structure to provide alternative force transmission path, thereby forming antiprogressive collapse force. In the case of initial failure of shear wall, C-shaped shear wall can form alternative path to diminish the vertical deformation of frame-shear structures. Final comparison shows that the structural seismic design can effectively improve their anticollapse performance.